Role of Rural Women in Farm Management Decision Making Process - U.D. Patil; T.B. Deokate; S.N . Patil (Journal of Agricultural Extension Management, 2025)
Rural women play a significant role in domestic and socio-economic life of the society. As per 2001 census, agriculture and allied industrial sectors employ as much as 89.5 per cent of total female labour. In the case of working population, rural female participation rate is 27.2 percent which is nearly thrice of the urban female participation rate (9.7 per cent)